What Drives Gig Workers’ Welfare in Indonesia? Evidence from a Panel Data Regression 2018–2023 - Andi Muh. Zulfadhil Zareka; Alfi Hidayatullah; Dara Sakina; Bunga Musva Cotva; Budiasih (Jurnal Ketenagakerjaan, 2025)
The rapid growth of digital technology has driven significant transformations in the labor market, marked by the emergence of the gig economy. While offering flexibility, gig workers is often accompanied by legal uncertainties and a lack of social protection, raising concerns about worker welfare. This study aims to identify the factors influencing gig workers' wages in Indonesia from economic, social, and digital perspectives. The analysis uses panel data from 34 provinces over the 2018–2023 period, sourced from BPS. The analytical method employed is the fixed effect model, corrected using the seemingly unrelated regression approach to address issues of heteroskedasticity and inter-regional correlation. The results show that inflation, human development index, open unemployment rate, ICT readiness, and ICT intensity significantly affect gig workers’ wages. ICT readiness has a positive impact, whereas the ICT intensity has a negative effect on wages. Meanwhile, ICT skills do not show a significant influence. This study highlights the need for inclusive digital policies and strengthened worker bargaining power to build a sustainable gig economy ecosystem.